Adopsi Blended Learning untuk Mahasiswa Perguruan Tinggi dengan Menggunakan Pendekatan Extended UTAUT - Munsharif, Achmad; Pramana, Edwin; Zaman, Lukman (Rekayasa, 2024)
This research aims to determine the factors that influence the understanding of students' intentions in higher education in using blended learning and determine the relationship between factors in the theoretical model. This research was conducted because there is still a lack of research in the world that discusses the application of blended learning in higher education in developing countries such as Indonesia. Blended learning in higher education during the Covid-19 pandemic is still needed today because educational institutions have limited space to accommodate students and to follow technological development trends and utilize them in the world of education. Questionnaires distributed via Google Form were used to collect data. The sample was 541 blended learning users from various universities in Indonesia. All variables from the theoretical model are measured using existing scales. Structural Equation Model (SEM) is used to analyze the theoretical model. SPSS and Amos are used as analysis support software. This research contributes to the theoretical understanding of Blended Learning adoption as well as practices and guidelines for higher education institutions to successfully implement Blended Learning in their institutions. Of the eight initial hypotheses, there are seven hypotheses that are very significant. The three factors with the largest magnitude are effort expectancy, performance expectancy and system functionality. Effort expectancy is the most influential factor in implementing blended learning in higher education institutions.